2013
DOI: 10.1002/hup.2307
|View full text |Cite
|
Sign up to set email alerts
|

Inferring about individual drug and schizotypy effects on cognitive functioning in polydrug using mephedrone users before and after clubbing

Abstract: Results suggest that polydrug use and depressive symptoms in the general population negatively affect cognition. For schizotypy, only elevated cognitive disorganisation showed potential links to a pathological cognitive profile previously reported along the psychosis dimension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 144 publications
(192 reference statements)
0
12
0
Order By: Relevance
“…Both the analytical and pharmacological characterization of mephedrone has been well documented in the scientific literature [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and studies focusing specifically on synthesis related by-products have also been conducted. [38] The cathinone molecular scaffold gives rise to a large range of biologically active compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the analytical and pharmacological characterization of mephedrone has been well documented in the scientific literature [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and studies focusing specifically on synthesis related by-products have also been conducted. [38] The cathinone molecular scaffold gives rise to a large range of biologically active compounds.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] Data from human-based studies have also suggested that mephedrone impairs working memory acutely, induces stimulantlike effects in users comparable to MDMA, [17,18] and disrupts cognitive function and verbal fluency. [19] It has been reported that mephedrone can be administered in a number of ways including orally, nasal insufflation, intramuscular injection, intravenous injection, rectal insertion, inhalation, or vaporization. [20,21] Fatalities associated with its use have been reported throughout the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Polysubstance use is posing a global public health risk due to unknown modes of action of individual NPS, unexpected multiple intoxications and inability to identify the causative substance(s) (Aromatario, Bottoni, Santoni, & Ciallella, ; Council of Europe, ; Herzig, Brooks, & Mohr, ; INCSR, ). Users favour unpredictable effects of polydrug use and seek maximum mind alteration and disinhibition, known as “the garbage head syndrome” (Iudici, Castelnuovo, & Faccio, ).…”
Section: Resultsmentioning
confidence: 99%
“…It is thus possible that substances (e.g., illicit as well as licit) influenced the relationship between schizotypal symptoms and the cognitive functions assessed in these experiments (3840). In particular, our results suggest that cannabis may be more relevant than schizotypy for cognitive attenuations in verbal short-term memory, and alcohol may be more relevant than schizotypy for cognitive attenuations in working memory (82).…”
Section: Discussionmentioning
confidence: 99%
“…We expected that both illicit and licit drug use might be more important than schizotypy to explain variance in cognitive performance (3840). If schizotypy would additionally or instead explain variance in cognitive performance, we would expect the cognitive disorganization dimension (2527) and/or positive schizotypy dimension (24, 41, 42) to be more relevant than the negative schizotypy dimension (27, 37, 4244) that frequently resulted in heterogeneous findings.…”
Section: Introductionmentioning
confidence: 99%